(–)-Epicatechin Provides Neuroprotection in Sodium Iodate-Induced Retinal Degeneration - Peng, Manjuan; Zhou, Xuezhi; Yao, Fei; Li, Haibo; Song, Weitao; Xiong, Siqi; Xia, Xiaobo (Frontiers in Medicine, 2022)
Oxidative stress, mitochondrial impairment, and pathological amyloid beta (Aβ) deposition are involved in the pathogenesis of dry age-related macular degeneration (AMD). The natural flavonoid (−)-epicatechin (EC) is known to be an antioxidant and neuroprotective compound. Whether EC plays a therapeutic role in AMD is unknown. In this work, we aimed to assess the efficacy and molecular mechanisms of EC against sodium iodate (NaIO3)-induced retinal degeneration in C57BL/6 mice via bioinformatic, morphological, and functional methods. We demonstrated that EC had no toxic effects on the retina and could ameliorate retinal deformation and thinning. EC treatment prevented outer retinal degeneration, reduced drusen-like deposits, increased b-wave amplitude in electroretinography, blocked retinal gliosis, and increased the number and quality of mitochondria. Importantly, EC increased the protein expression of OPA1 and decreased the expression of PINK1, indicating the role of EC in mitochondrial fusion that impaired by NaIO3. Moreover, EC downregulated APP and TMEM97 levels, upregulated PGRMC1 levels, and reduced subretinal Aβ accumulation. This study illustrated that EC, which may become a promising therapeutic strategy for AMD, prevented NaIO3-induced retinal degeneration, and this improvement may be associated with the mitochondrial quality control and the TMEM97/PGRMC1/Aβ signaling pathway.